Cut-off value of strut-vessel distance for the resolution of acute incomplete stent apposition in the early phase using serial optical coherence tomography after cobalt-chromium everolimus-eluting stent implantation. Issue 6 (June 2020) - Oda, Hideto; Itoh, Tomonori; Sasaki, Wataru; Uchimura, Yohei; Taguchi, Yuya; Kaneko, Kyosuke; Sakamoto, Tsubasa; Goto, Iwao; Sakuma, Masafumi; Ishida, Masaru; Kikuchi, Tatsuo; Terashita, Daisuke; et al.
Highlights: Cut-off value of the strut vessel (SV) distance to predict incomplete-stent-apposition (ISA) resolution was determined. Prevalence of the persistent ISA was different for each plaque. Persistent ISA of calcified plaque was easy to remain regardless of SV distance. Abstract: Objective: The purpose of this study was to identify a cut-off value to predict the resolution of incomplete-stent-apposition (ISA) after cobalt-chromium everolimus-eluting stent (CoCr-EES) implantation at early follow-up. Background: To date, appropriate stent apposition at the acute period using intracoronary imaging has been recommended because persistent ISA is considered to be a risk factor for stent thrombosis. We examined the indices for resolving acute ISA. In particular, we determined the cut-off value for strut vessel distance (SV-distance) as visualized by optical coherence tomography (OCT) at 8 months after CoCr-EES implantation. However, the cut-off value of SV-distance for the earlier resolution of ISA is unclear. Methods: A total of 95 cases and 103 stents were registered in the MECHANISM Elective substudy. The SV-distance was measured at the deepest site of the target malapposition and every 1 mm from the proximal edge to the distal edge of the mal-apposed area using OCT. Cut-off values for ISA resolution at 1 and 3 months were estimated by SV-distance using receiver operating characteristic analysis. Results: The total number of analyzed struts was 14, 418 at the 1-month follow-up and 11, 986 at the 3-month follow-up. The optimal SV-distance cut-off values just after stent implantation to predict ISA resolution were 185 µm at the 1-month follow-up and 195 μm at the 3-month follow-up. Conclusion: For resolution of ISA, SV-distance cut-off values of 185 µm at 1 month postimplantation and 195 μm at 3 months postimplantation can be used as the index of endpoint of the percutaneous coronary intervention.